2017
DOI: 10.5455/njppp.2018.8.1143618112017
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of efficacy and safety of metformin and vildagliptin versus metformin and glimepiride in patients of Type 2 diabetes mellitus

Abstract: Background: Diabetes mellitus is a heterogeneous chronic metabolic disorder principally characterized by persistent hyperglycemia resulting from defects in insulin action and/or insulin secretion. In course of time, prolonged hyperglycemia and associated metabolic aberrations result in tissue toxicity manifested as accelerated atherosclerosis, renoretinal microangiopathy, and neuropathy leading to a variety of vascular, neurological, and focal complications. Aim and Objective: The aim of this study is to evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…Few studies have reported conflicting results of both vildagliptin and glimepiride added to metformin regarding the efficacy of antidiabetic agents and safety outcomes. [ 9 12 13 16 ]…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Few studies have reported conflicting results of both vildagliptin and glimepiride added to metformin regarding the efficacy of antidiabetic agents and safety outcomes. [ 9 12 13 16 ]…”
Section: Discussionmentioning
confidence: 99%
“…These findings were consistent with the previous studies which evaluated early initiation of vildagliption or glimepiride add-on to metformin associated with durability in glycemic control. [ 12 ] This indicates both treatments were effective in antihyperglycemic effects and early initiation of this combination therapy would be a good approach to manage T2DM in drug naïve patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations